PHYTOCHEMICALS AND RADICAL SCAVENGER ACTIVITY OF KAYU JAWA (LANNEA COROMANDELICA) AND SALAM (SYZYGIUM POLYANTHUM) LEAF STEEPING AND THE COMBINATED RATIONAL - Nasrudin Nasrudin; Abraham Rahman; Nurlansi Nurlansi; Rahmanpiu Rahmanpiu; Damhuri Damhuri; Bilal Subchan Agus Santoso; Kismawati Kismawati; Jusna Jusna; Lulu Rahmatia (Universitas Muhammadiyah Magelang, 2021)
Herbal medicine as a traditional medicine based on local wisdom in the Covid 19 pandemic is the alternative for the community to keep the health of the body. Specific drugs for the cure of Covid-19 disease have also not been found yet so the death of Covid-19 patients remainsat anytime. In this case this study aims to know the content of secondary metabolite compounds and radical scavenger activity of “kayu jawa” (L. coromandelica) leaf steeping and “Salam” (S. polyanthum) leaves from Southeast Sulawesi as well as their rational combination based on the radical scavenger activity of DPPH (2,2-difenyl-1-picrilhydrazil). The analysis of the content of secondary metabolite compounds in the steeping of DKJ (Daun Kayu Jawa) and DS (Daun Salam) is applied by phytochemical method and radical scavenger activity is determined by the DPPH method. The main focus of steeping is determined by the approach of the picnometer. The combination of DKJ and DS is made each with 6 variations based on the IC50 steeping value, then converted in the form of weight (grams) of DKJ and DS powder so that 36 combinations are obtained. The result of phytochemical analysis of DKJ and DS steeping showed the presence of flavonoids, saponins and polyphenols, except tannins only exist in the steeping of DS. The radical scavenger activity of DKJ and DS steeping showed IC50 values of 408.95 ± 0.075 µg/mL and 259.05 ± 0.092 µg/mL. The combination that showed the highest DPPH radical scavenger activity of 88.050.03% occurred in the combination of E1 with a ratio of 2IC50 DK: 1/8IC50DS (1,089: 0.128) grams. DPPH radical scavenger activity approaching 50% occurs in the combination of A2 and B1 with a ratio of 1/8IC50 DKJ: ¼IC50DS (0.068:0.256) grams and ¼IC50 DKJ: 1/8IC50DS (0.136:0.128) grams with values of (49.11 0.04) % and (52.87 0.05) % respectively.